Financial Management System for Final-Year University Students Implementing a Rule-Based Method on the Android Platfor - Azzahra Iskandar, Farah; Fikry, Muhammad; Rosnita, Lidya (International Journal of Engineering, Science and Information Technology, 2025)
Final-year students face significant financial challenges due to limited income and low financial literacy. This often leads to uncontrolled spending, lack of awareness about financial habits, and imbalanced income and expenses. This study proposes a rule-based financial management system to help students organize, monitor, and analyze their finances. The analysis shows that students' main expenses are food, transportation, and housing, with financial risks arising from irregular financial recording and overspending. The proposed system includes features like expense categorization, budget limits, monthly reports, notifications for unusual spending, and reminders to record finances. Applying a rule-based approach, the system offers personalized recommendations, such as budget control for specific categories and early warnings for disproportionate expenses. This application aims to improve financial awareness, help students prioritize spending, and reduce financial risks. It also serves as a financial education tool to support students in achieving financial stability as they transition into professional life.